Analisis Postur Pekerja Welding Bengkel Pipa Menggunakan Metode RULA dan REBA dengan Pendekatan Fuzzy Logic - Ayutatila, Bahiragita Adristi; Islami, Mega Cattleya Prameswari Anissa (Universitas Harapan Medan, 2025)
PT. XYZ is a national company engaged in the maritime industry, including shipbuilding and repairs. In its production activities, there are welding activities in the pipe workshop. In these activities, there are workers who experience complaints in certain parts of the body because they continue to work in less ergonomic positions. This problem is usually caused by poor work posture, lifting heavy loads, or lack of work facilities that support comfort. These complaints, if not handled properly, can increase the risk of musculoskeletal disorders that have the potential to reduce worker productivity. In solving the problems that occur, worker posture measurements are carried out using the RULA and REBA methods with the Fuzzy Logic approach to determine the level of MSDS risk. The results of the RULA method work posture measurement were 7 and the REBA method was 8. The use of these two work posture measurement methods is used as input variables in the fuzzy logic approach. The results of the output value for the MSDs risk level are 6.92 where this value is included in the high category. From the results of the processing above, it can be an evaluation of improvements for non-ergonomic work postures and work facilities.